Strain engineering of oxide thin films for photocatalytic applications. (June 2020) - Liu, Zhao; Menéndez, Cesar; Shenoy, Joel; Hart, Judy N.; Sorrell, Charles C.; Cazorla, Claudio
Abstract: Photocatalytic materials are pivotal for the implementation of disruptive clean energy applications such as conversion of H2 O and CO2 into fuels and chemicals driven by solar energy. However, efficient and cost-effective materials able to catalyze the chemical reactions of interest when exposed to visible light are scarce due to the stringent electronic conditions that they must satisfy. Chemical and nanostructuring approaches are capable of improving the catalytic performance of known photoactive compounds however the complexity of the synthesized nanomaterials and sophistication of the employed methods make systematic design of photocatalysts difficult. Here, we show by means of first-principles simulation methods that application of biaxial strain, η, on semiconductor oxide thin films can modify their optoelectronic and catalytic properties in a significant and predictable manner. In particular, we show that upon moderate tensile strains CeO2 and TiO2 thin films become suitable materials for photocatalytic conversion of H2 O into H2 and CO2 into CH4 under sunlight. The band gap shifts induced by η are reproduced qualitatively by a simple analytical model that depends only on structural and dielectric susceptibility changes. Thus, epitaxial strain represents a promising route for methodical screening and rational design of photocatalytic materials. Graphical abstract: Image 1 Highlights: Under moderate tensile strains of 2–3% CeO2 and TiO= become promising photocatalytic materials. A simple analytical model is introduced that reproduces the band gap shifts induced by biaxial strain. Strain engineering emerges as a powerful approach to improve the photocatalytic activity of oxide semiconductors.